Extending the Developmental Interpretation of Delusions and Hallucinations.. - Glick, Marion (1988)
Keywords: dept.psy; faculty_collection; sabbatical_report

Is paranoid schizophrenia really camouflaged depression - Zigler, Edward; Glick, Marion (American Psychologist, 1988)
Keywords: dept.psy

Effect of lysine-8-vasopressin on retention and retrieval of a discrimination reward task in the rat. - Mulvey, Debra J; Watt, Jean M; Mcewen, Barbara B; Flannelly, Linda M (Behavioral Neuroscience, 1988)
The effect of vasopressin on memory of a brightness discrimination reward task was investigated in 20 male Sprague-Dawley rats. Two measures of retention were used: resistance to extinction and savings scores on a reacquisition task given 45 days after the completion of extinction training. The effect of the peptide on both memory consolidation and retrieval was assessed. There were two major findings: (a) The peptide enhanced memory consolidation of the task whether measured after a short time interval (6 days) or after a long time interval (45 days after completion of extinction training) using a measure of trials to relearn the task, and (b) the peptide had no effect on memory retrieval. These results were compared to those of other studies designed to access memory consolidation and retrieval on appetitive tasks. The mechanisms of the peptide's effect on memory was briefly discussed with respect to three theories on the subject. This study extends the vasopressin research on memory consolidation by suggesting that it pertains to appetitive as well as to aversive tasks.
Keywords: Animal; Appetitive Behavior; Brain; Conditioning, Operant; Discrimination Learning; Extinction (Psychology); Lypressin; Male; Memory; Mental Recall; Motivation; Orientation; Rats; Rats, Inbred Strains; Retention (Psychology); animal experiment; controlled study; dept.psy; lypressin; male; memory consolidation; memory retrieval; nonhuman; psychological aspect; psychophysiology; rat; reward